Exchange Rate Unification, the Equilibrium Real Exchange Rate, and Choice of Exchange Rate Regime : The Case of the Islamic Republic of Iran. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper reviews recent developments in the exchange system in the Islamic Republic of Iran and in the real effective exchange rate (REER). It also considers the determinants of the REER in connection with the choice of exchange regime after unification. The study illustrates how economic policy variables and exogenous shocks affect the real exchange rate primarily through the fiscal balance, and consequently, the savings-investment gap. It further illustrates that the appropriate level of REER and its medium-term path depend upon the mix of monetary, fiscal, and structural policies that underpin the evolution of inflation, balance of payments, and productivity growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet